Application of Good Governance Principles in Improving the Performance of the State Civil Apparatus (ASN) at the Pesisir Bukit Subdistrict Office, Sungai Penuh City - Khairi, Awal (The Future of Education Journal, 2025)
Application of Good Governance Principles in Improving the Performance of the State Civil Apparatus (ASN) at the Pesisir Bukit Subdistrict Office, Sungai Penuh City. This research aims to find out how the principles of good governance are implemented in improving the performance of the State Civil Apparatus (ASN) at the Pesisir Bukit Subdistrict Office, Sungai Penuh City. The type of research that the author uses is Qualitative research with the Observation Method, where the researcher focuses more on observing the problems that occur so that the researcher relies on data obtained in the field and then analyzes Winartha (2006: 155). Data collection in this research used observation, interview and documentation methods. This research uses data analysis techniques used in qualitative field research in accordance with Nursapia's opinion, namely through data reduction, data presentation, and drawing conclusions. The results of his research show that the application of Good Governance Principles has an important role in improving the performance of the State Civil Apparatus (ASN) at the Pesisir Bukit Subdistrict Office, Sungai Penuh City.